2005
DOI: 10.1002/ajmg.a.30622
|View full text |Cite
|
Sign up to set email alerts
|

Down syndrome and comorbid autism‐spectrum disorder: Characterization using the aberrant behavior checklist

Abstract: To report on the cognitive and behavioral attributes of 61 children with Down syndrome (DS) and autistic-spectrum disorder (ASD) according to DSM-IV criteria; to determine the utility of the aberrant behavior checklist (ABC) to characterize these subjects for research purposes; and to test the hypothesis that subjects with DS + ASD could be distinguished from their typical DS peers using the ABC. Cross-sectional design. Cases with DS + ASD (N = 61), comparison group of DS + stereotypy movement disorder (SMD) (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
126
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 133 publications
(151 citation statements)
references
References 35 publications
23
126
1
1
Order By: Relevance
“…Even if the present study confirmed previous data of a relatively high prevalence of Anxiety disorder also in individuals with DS (more than 14%), results from the direct comparison between participants with DS and participants with WS support evidence indicating how Anxiety disorder is less common in DS than in other populations with ID [52][53][54].…”
Section: Discussionsupporting
confidence: 73%
“…Even if the present study confirmed previous data of a relatively high prevalence of Anxiety disorder also in individuals with DS (more than 14%), results from the direct comparison between participants with DS and participants with WS support evidence indicating how Anxiety disorder is less common in DS than in other populations with ID [52][53][54].…”
Section: Discussionsupporting
confidence: 73%
“…Since similar studies have not been reported in other developmental disorders associated with ASD, it is not possible at this point to determine the specificity of the social avoidance-ASD correlation in FraX. Nevertheless, our recent work in Down syndrome indicates that social withdrawal scales are useful for distinguishing subjects with ASD from individuals with other behavioral conditions associated with this genetic disorder [Capone et al, 2005]. On the other hand, data on other behavioral measures suggest that in idiopathic ASD, there is a major link between social indifference or aloofness, but not avoidance, and the diagnosis of ASD [Eaves et al, 1994;Amaral et al, 2003].…”
Section: Discussionmentioning
confidence: 86%
“…This study focused primarily on the CBCLw subscale, which we and others [Hatton et al, 2002] have successfully applied to FraX populations. The ABC-C [Aman and Singh, 1986] is also a widely used parental report that we have applied to the study of ASD in FraX Kaufmann et al, 2004] and Down syndrome [Capone et al, 2005]. The ABC-C evaluates inappropriate and maladaptive behaviors in 3 to 18-year-old individuals with developmental disabilities through five subscales: Irritability, Lethargy/ Social withdrawal (ABCsw), Stereotypic behavior, Hyperactivity, and Inappropriate speech.…”
Section: Subjectsmentioning
confidence: 99%
“…30 Autism is 10 times more common in children with Down syndrome than in the general population. The majority of reported individuals with comorbid autism and Down syndrome are male, 31 although this may reflect underreporting by professionals who expect autism to be less common in females.…”
Section: Down Syndromementioning
confidence: 99%
“…Recent studies have shown that the co-occurrence of Down syndrome with ASD is associated with significantly higher total scores on the Aberrant Behavior Checklist and Autism Behavior Checklist, in agreement with earlier reports of a link between the degree of low cognitive function and severity of autistic-like behaviours. 30 Finally, Molloy et al 33 showed that, among children with trisomy 21, brain function (i.e. communication, and cognitive and adaptive behaviour skills) is significantly more impaired in those with autism than in those without autism.…”
Section: Down Syndromementioning
confidence: 99%